2018
DOI: 10.1159/000489493
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial Comparing Embryo Transfers of Cases with and without Catheter Rotation during Its Withdrawal

Abstract: Objective: To compare embryo transfer (ET) technique based on catheter rotation during its withdrawal in cases with unexplained infertility in a prospective, randomized trial (NCT03097042). Methods: Two hundred intracytoplasmic sperm injection (ICSI) patients undergoing ET with cleaving or blastocyst-stage fresh embryos were randomized into 2 groups: cases with (n = 100), and without (n = 100) catheter rotation during its withdrawal. Groups were matched for age and some clinical parameters. A soft catheter was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…There was no evidence that catheter rotation following ET had a positive effect on pregnancy outcomes. These results were different from those reported by Yayla Abide et al, 12 and we attributed this discrepancy to the small number of samples in their study. On average, ET is performed on day 5 after ovarian stimulation in our clinic at the present time.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…There was no evidence that catheter rotation following ET had a positive effect on pregnancy outcomes. These results were different from those reported by Yayla Abide et al, 12 and we attributed this discrepancy to the small number of samples in their study. On average, ET is performed on day 5 after ovarian stimulation in our clinic at the present time.…”
Section: Discussioncontrasting
confidence: 99%
“…1 Rotation of embryo transfer catheter during withdrawal. 12 that aspiration of cervical mucus through the endocervical canal using sterile cotton swabs or a catheter improved clinical outcomes, 8,9 and others showed no change in pregnancy results with the use of cervical brush removal. 13 A meta-analysis of Craciunas of medium-and low-quality studies showed that removing cervical mucus before ET was of little benefit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations